The Book of Sorrows - Wangerin, Walter (San Francisco : Harper & Row, 1985)
In the aftermath of the terrible conflict with the dreaded Wyrm, Chauntecleer, Pertelote, and the other inhabitants of the Coop try to piece together their shattered lives until the Wyrm once again insinuates himself with dire consequences for all.
Keywords: Animals -- Fiction; Fantasy